Data from: The effects of hybridization and parasite infection on predation survival and behaviour of endangered landlocked salmon – implications for genetic rescue ... - Eronen, Aslak; Janhunen, Matti; Hyvärinen, Pekka; Kortet, Raine; Karvonen, Anssi (Dryad, 2025)
A prerequisite of genetic rescue in endangered and genetically depauperate populations is to pre-evaluate between possible pros and cons of hybridization for the life history and survival of the target population. We hybridized critically endangered Saimaa landlocked salmon (Salmo salar m. sebago) with one of its geographically closest relatives, anadromous Baltic salmon. In two experiments conducted in semi-natural streams during overwintering (at age 1.5 years) and in early summer (age 2+), we studied how hybridization and infection of eye parasites (Diplostomum pseudospathaceum) affected fish survival under predation from Northern pike (Esox lucius). Additionally, we recorded movements of the juvenile salmon to explore the effect of hybridization and infection on antipredatory behaviour (movement activity and habitat use). Among the uninfected groups, mortality of hybrid salmon was significantly lower (14.5%) compared to purebred landlocked salmon (37.2%), supporting a positive effect of hybridization ... : In October 2018, we hybridized the critically endangered landlocked salmon of the Vuoksi watershed, Finland (Salmo salar m. sebago Girard, 1853) with a geographically close Baltic anadromous salmon (Salmo salar L. 1758, population spawning in river Kymijoki, Finland, but originally from river Neva, Russia). Parental fish consisted of 15 males and 15 females from both populations, with eggs from each female being fertilized with one male from its own population and the other part with one male from the other population. Correspondingly, equal portions of milt from each male were used to fertilize eggs of one female from its own population and of one female from the other population (n = 60 full-sibling families, 15 per crossing group). This resulted in four crossing groups: purebred landlocked salmon (LL×LL), landlocked salmon females crossed with anadromous salmon males (LL×BA, hybrid), anadromous salmon females crossed with landlocked salmon males (BA×LL, hybrid), and purebred anadromous salmon (BA×BA). ...